Finding the Truth Behind the Language - Muji Muji (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Finding the truth of the behavior expressed through language is not easy. It is due to the meaningless expression that the speaker tends to use. It often appears irrelevant as the first intention was A, but the meaning then referred to B, C, D or even E. Both spoken and written languages sometimes do not reflect the actions being done as in a debate, interview, advertisement, and poster, the content does not match what the speaker tried to deliver. In other words, the meaning expressed or written is uncertain. Through the phenomenological research, it is found to be a problematic language. Through the act of understanding the meaning and its connection to people in certain situations, they could try to express a variety of languages. Through the observation, interview and documentation, the data were found as (1)